(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2016)
The current work was performed at the Scientific Station Pedro Franco Dávila, located in the Jauneche precinct, Province of Los Rios, coastal Ecuador. The aim of this study was to estimate the species richness of anura in this Research Station and present a short description of external morphology of each species found. Six visits were conducted from May to August 2015, the estimate of catching effort was 69,600 hours-meters. The methodology used was basic procedures (directindirect); direct was based on the intensive search by visual encounter and as indirect methods pitfall traps were used. Also, day and night tours on existing trails and routes perpendicular to the trails from 5 to 30 meters were conducted. Eighty-six anuran species were recorded belonging to 5 families, 13 genera and 12 species. Of the species reported the highest species richness is for Craugastoridae family with 50 individuals and the dominant species was Pristimantis achatinus. Leptodactylidae families, Hylidae, Craugastoridae, Bufonidae, Dendrobatidae were also recorded.